2019
DOI: 10.1155/2019/5485630
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Varying Compressive Strength Model of Aeolian Sand Concrete considering the Harmful Pore Ratio Variation and Heterogeneous Nucleation Effect

Abstract: The aim of this study was to analyze the influence mechanism of aeolian sand on the mechanical property of concrete and establish the time-varying compressive strength model. Test studies on the development of concrete’s compressive strength with aeolian sand from the Mu Us Desert were carried out. Influence mechanism of aeolian sand on the strength of concrete was revealed by using the nuclear magnetic resonance (NMR) to analyze the pore ratio and structures of aeolian sand concrete (ASC) and using the X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Particle size led to the reduction in the distance between nucleation sites and cement particles, promoted the hydration reaction of cement, and resulted in the generation of more hydration products, which not only optimized the matrix structure, but also enhanced the compressive strength of the matrix [ 31 , 32 ]. Furthermore, smaller desert sand particles and thinner slurry thickness can improve the structure and strength of the interfacial transition zone by inhibiting ion migration in the interfacial transition zone [ 33 ]. Moreover, the CaO/SiO 2 ratio (calculated from Table 1 : 0.166) is larger for desert sand compared to that for river sand and standard sand, which also exhibits a positive effect on the development of compressive strength [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Particle size led to the reduction in the distance between nucleation sites and cement particles, promoted the hydration reaction of cement, and resulted in the generation of more hydration products, which not only optimized the matrix structure, but also enhanced the compressive strength of the matrix [ 31 , 32 ]. Furthermore, smaller desert sand particles and thinner slurry thickness can improve the structure and strength of the interfacial transition zone by inhibiting ion migration in the interfacial transition zone [ 33 ]. Moreover, the CaO/SiO 2 ratio (calculated from Table 1 : 0.166) is larger for desert sand compared to that for river sand and standard sand, which also exhibits a positive effect on the development of compressive strength [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Benabed et al [3] utilised ultra-fine sand to prepare a self-compacting mortar, and Padmakumar et al [4], Jiang et al [5] and Luo et al [6] prepared concrete using aeolian sand as a fine aggregate and found that aeolian sand can be effectively used as a substitute material for concrete and mortar fine aggregates. Li et al [7,8], Dong et al [9], and Al-Harthy et al [10] used aeolian sand to replace river sand to prepare concrete and found that the slump rate and strength of the concrete first increased and then decreased with an increase in the aeolian sand content. However, Guettalla [11] and El-Sayed et al [12] concluded that the strength of concrete decreases with an increase in aeolian sand content, which means that aeolian sand only has negative effects on the technical properties of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers and engineers have begun to use desert sand as a substitution for artificial sand to produce concrete, as desert sand has the potential to fill the gap between artificial sand particles, the distribution of which is always discontinuous due to the lack of fine particles [10,11]. Many strength prediction models have been built based on experimental statistics or various theories, for example, heterogeneous nucleation [12], harmful capillaries [13], and compressible accumulation [14]. Most research about desert sand applications in concrete technology took the desert sand substitution ratio as being univariate, while the sand ratio and other indices of the mix proportion were controlled to be constant.…”
Section: Introductionmentioning
confidence: 99%